Hepatitis B surface antigen incorporated in dissolvable microneedle array patch is antigenic and thermostable. (November 2017) - Poirier, Danielle; Renaud, Frédéric; Dewar, Vincent; Strodiot, Laurent; Wauters, Florence; Janimak, Jim; Shimada, Toshio; Nomura, Tatsuya; Kabata, Koki; Kuruma, Koji; Kusano, Takayuki; Sakai, Masaki; et al.
Abstract: Alternatives to syringe-based administration are considered for vaccines. Intradermal vaccination with dissolvable microneedle arrays (MNA) appears promising in this respect, as an easy-to-use and painless method. In this work, we have developed an MNA patch (MNAP) made of hydroxyethyl starch (HES) and chondroitin sulphate (CS). In swines, hepatitis B surface antigen (HBsAg) formulated with the saponin QS-21 as adjuvant, both incorporated in HES-based MNAP, demonstrated the same level of immunogenicity as a commercially available aluminum-adjuvanted HBsAg vaccine, after two immunizations 28 days apart. MNAP application was associated with transient skin reactions (erythema, lump, scab), particularly evident when the antigen was delivered with the adjuvant. The thermostability of the adjuvanted antigen when incorporated in the HES-based matrix was also assessed by storing MNAP at 37, 45 or 50 °C for up to 6 months. We could demonstrate that antigenicity was retained at 37 and 45 °C and only a 10% loss was observed after 6 months at 50 °C. Our results are supportive of MNAP as an attractive alternative to classical syringe-based vaccination.